SUBMARINE PATHS OF THE PARK NATIONAL CAHUITA: BIOLOGICAL DESCRIPTION - Palacios-Martínez, Gerardo E. (2009)
This survey provides biological information regarding the underwater trails of Cahuita National Park, and identifies the most common species present. The biological description of the flora and fauna are based on line transects and direct observation. The Perezoso underwater trail had 40% live coral cover, of which the Lobe coral (Siderastrea siderea) was the most common; the most common species of fish belonged to the family Pomacentridae. The long spined sea urchin (Diadema antillarum) was the most common among the invertebrates, and the algae recorded belonged to the genera Dictyota and Halimeda. The coral species  Siderastrea siderea and Agaricia agaricites were the most common corals of the Perezoso and Eduardo underwater trails.